2018
DOI: 10.1371/journal.pone.0190932
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect and possible mechanism of a Pseudomonas strain QBA5 against gray mold on tomato leaves and fruits caused by Botrytis cinerea

Abstract: The fungal pathogen Botrytis cinerea causes gray mold disease on various hosts, which results in serious economic losses. Over the past several decades, many kinds of fungicides have been used to successfully control the disease. Meanwhile, the uses of fungicides lead to environmental pollution as well as a potential threat to the human health by the chemical residues in tomato fruit. Also, the gray mold disease is difficult to control with fungicides. Therefore, exploring alternative measures such as biologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 41 publications
(50 reference statements)
0
18
0
Order By: Relevance
“…Pathogens that cause major economic losses include the necrotrophic fungus Botrytis cinerea. This fungus, which is known to cause gray mold, affects a wide range of host plants and infects over 200 plant species, including important horticultural crops [ 3 , 4 ]. The disease process of B. cinerea is affected by many pathogenicity determinants, such as host cell wall degradation, cell death and host defense avoidance [ 5 , 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pathogens that cause major economic losses include the necrotrophic fungus Botrytis cinerea. This fungus, which is known to cause gray mold, affects a wide range of host plants and infects over 200 plant species, including important horticultural crops [ 3 , 4 ]. The disease process of B. cinerea is affected by many pathogenicity determinants, such as host cell wall degradation, cell death and host defense avoidance [ 5 , 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Botrytis cinerea [teleomorph: Botryotinia fuckeliana (de Bary) Whetzel] is a necrotrophic fungi known to be the cause of grey mould. These fungi can infect more than 200 plant species, including horticulturally important crops ( Gao et al, 2018 ). Therefore, it has significant economic relevance, causing huge economic losses ( Dean et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it has significant economic relevance, causing huge economic losses ( Dean et al, 2012 ). The ability to produce conidiophores that contain conidia gives it the ability to remain quiescent until conditions are favourable enough to produce the infection ( Gao et al, 2018 ). The production of lytic enzymes along with other phytotoxic metabolites induces cell death in plant tissues, mainly affecting those in a state of senescence or with wounds on their surface ( Finiti et al, 2014 ; Gonzalez-Fernandez et al, 2015 ; Yu et al, 2015 ; Yahaya et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…It needs to be investigated whether MSB was still effective to cope with much higher disease pressure caused by more than 2 × 10 5 conidia/ml of B. cinerea , because much higher disease pressure of B. cinerea can diminish protective effect of MSB on tomato leaf grey mould. More efficient grey mould control by MSB-pretreatment against the lower diseases suggests that reducing inoculum density of B. cinerea by applying other eco-friendly agents such as beneficial microbes and/or plant defence activators, may improve MSB-mediated grey mould control efficacy during tomato production under a protected greenhouse environment ( Elad et al, 1994 ; Gao et al, 2018 ; Sivakumaran et al, 2016 ; Vicedo et al, 2009 ). It also suggested that repetitive pretreatment with MSB at least two times efficiently increased protection efficacy against tomato grey mould without phytotoxic side effect, showing more decreased grey mould lesions by MSBpretreatment.…”
Section: Discussionmentioning
confidence: 99%
“…Cell-free supernatant of Pseudomonas sp. QBA5 directly disrupted B. cinerea conidia by destroying plasma membrane integrity, and inhibited conidial germination and germ-tube elongation ( Gao et al, 2018 ). In vitro and in planta destructive nature of MSB to B. cinerea conidia as well as conidial stress responses remains elucidated.…”
Section: Discussionmentioning
confidence: 99%